2015
DOI: 10.4049/jimmunol.1402755
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Sequence Requirements for Oligodeoxyribonucleotides Activating Human TLR9

Abstract: Synthetic oligodeoxyribonucleotides (ODNs) containing CpG (unmethylated deoxycytidylyl-deoxyguanosine dinucleotide) motifs activate endosomal TLR9. The nucleotide sequence, length, and dimerization properties of ODNs modulate their activation of TLR9. We performed a systematic investigation of the sequence motifs of B-class and C-class phosphodiester ODNs to identify the sequence properties that govern TLR9 activation. ODNs shorter than 21 nt and with the adenosine adjacent to the cytidine-guanosine (CG) dinuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(104 citation statements)
references
References 45 publications
(85 reference statements)
4
100
0
Order By: Relevance
“…Our previous systematic analysis of the minimal sequence requirements for ODNs that activate hTLR9 (minH) confirmed that the 59TCG motif is essential for TLR9 activation but not sufficient (28), as indicated in the design of commonly used ODN2006 PTO (10,18,27,35,36). The ODNs with a 59TCG motif activate hTLR9 more effectively than mTLR9 as observed for the m109 and m127.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our previous systematic analysis of the minimal sequence requirements for ODNs that activate hTLR9 (minH) confirmed that the 59TCG motif is essential for TLR9 activation but not sufficient (28), as indicated in the design of commonly used ODN2006 PTO (10,18,27,35,36). The ODNs with a 59TCG motif activate hTLR9 more effectively than mTLR9 as observed for the m109 and m127.…”
Section: Discussionmentioning
confidence: 92%
“…The single CG motif within the minM ODN is sufficient to effectively activate mTLR9 in comparison with the two CpGs required for hTLR9 (Fig. 5D) (28). The minimal sequence requirements for the ODN that activates hTLR9 are the stringent 59TCGT motif and an additional CG motif 6-10 nt distant from the 59CG motif.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations